A Framework of Distributed Solar Blockchain as a Service. Issue 1 (1st July 2022) - Liang, Hao; Yu, Pengfei; Zhao, Xiaoran; Fu, Da
Abstract: Blockchain was combined with several other information technologies and computing concepts to create modern cryptocurrencies protecting through cryptographic mechanisms instead of a central repository or authority. A Framework of distributed solar Blockchain Service (DSBaaS) platform as a Service is designed to manage distributed solar energy system by adopting Blockchain as a Service (BaaS) platform. Base on the ability operation and maintenance features of BaaS, it is available to solve operational management, safety management, material management, project management, financial transactions management, transaction settlement and other related multi-agent transaction pain points. Providing new business models for implementing distributed solar energy production, transmission and utilization of effective coordination and management, it is a key component to forming clean, efficient, flexible and intelligent distributed solar energy system.